A novel SOI MESFET to spread the potential contours towards the drain. Issue 9 (1st September 2020) - Mohtaram, Mohaddeseh; Orouji, Ali Asghar
ABSTRACT: This paper presents a new structure of Metal Semiconductor Field Effect Transistor (MESFET) for high power applications. One of the problems that we face in the design of the MESFET devices is that in most cases, the increase of breakdown voltage is accompanied by a decrease in the saturation drain current. Our aim to propose this structure is to improve these two parameters simultaneously. Using the insulator region under the sides of the gate (IR) and the hide field plate (HFP) in the buried oxide (BOX) are the fundamental solution for improving these parameters. We named the proposed structure as spread potential contours towards the drain MESFET (SPC-MESFET). By applying the proposed structure, the drain current and the breakdown voltage improve 20 and 27 percent compared to a conventional structure (C-MESFET), respectively. Therefore, the proposed device has a higher maximum power density than the C-MESFET structure. Also, this idea reduces the gate capacitance and thus the frequency characteristics such as cut off frequency (fT ), maximum oscillation frequency (fmax ), and Maximum Available Gain (MAG) improve in comparison with the C-MESFET structure.